2019
DOI: 10.18632/aging.102467
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammation, anti-oxidative and anti-fibrosis properties of swertiamarin in cigarette smoke exposure-induced prostate dysfunction in rats

Abstract: Chronic cigarette smoke (CS) exposure induces prostate deficits. We previously found that swertiamarin had prostatic protective potential. This study was to investigate the possible protective effect of swertiamarin against CS-induced prostate dysfunction on human prostate epithelial cells, stromal cells and rats. Rat prostate collagen deposition and fibrosis were assessed by sirius red staining and measuring hydroxyproline content, as well as by qPCR and western blot analysis for fibrotic extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Swertiamarin is the active ingredient in many traditional Chinese medicines. Studies have shown that swertiamarin and its derivatives have anti-diabetes and anti-hyperlipidemia effects and can alleviate pathological neuropathic pain ( 189 ). However, its anti-diabetic mechanism is still unclear.…”
Section: Potential Treatment Options Related To the Inflammasomementioning
confidence: 99%
“…Swertiamarin is the active ingredient in many traditional Chinese medicines. Studies have shown that swertiamarin and its derivatives have anti-diabetes and anti-hyperlipidemia effects and can alleviate pathological neuropathic pain ( 189 ). However, its anti-diabetic mechanism is still unclear.…”
Section: Potential Treatment Options Related To the Inflammasomementioning
confidence: 99%
“…Cigarette smoking can cause inflammation in many tissues 13–16 . The effects of smoking on the bladder are complex and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking can cause inflammation in many tissues. [13][14][15][16] The effects of smoking on the bladder are complex and unclear. To date, accumulated evidence has shown there is a clear link between smoking and bladder cancer, and smoking can affect gene expression and induce local inflammation of bladder.…”
mentioning
confidence: 99%
“…They observed strong antioxidant activity based on the 2,2′‐azino‐bis (3‐ethylbenzothiazoline‐6‐sulfonic acid) ABTS and hydrogen peroxide assays. Moderate activity was observed in the deoxyribose and lipid peroxidation assays with low IC 50 values, where the total antioxidant capacity of swertiamarin was 4.51 mM ascorbic acid per gram, indicating its potent antioxidant effect (Chen et al, 2019). Patel et al demonstrated the antioxidant and lipid‐lowering properties of swertiamarin.…”
Section: Pharmacological Effectsmentioning
confidence: 99%